1991
DOI: 10.1007/bf02072624
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of oesophageal motility in children with psychomotor retardation and gastro-oesophageal reflux

Abstract: A group of 25 children affected by different degrees of psychomotor retardation (severe (n = 13); mild-moderate (n = 12)) and symptoms suggesting gastro-oesophageal reflux (GOR) underwent oesophageal manometry and oesophageal pH monitoring. Of these patients, 21 (84%) were affected by GOR. In all children with severe brain damage and GOR (12/13), oesophageal manometry showed marked motility abnormalities that persisted after cure of GOR. In patients with minor retardation and GOR (9/12), oesophageal manometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…These defects were also more prevalent with increasing severity of disease [12,14,19,20,26]. In contrast, Sondheimer [17] reported few motility defects in infants with GERD but found that these infants swallowed less frequently, particularly during sleep.…”
Section: Esophageal Volume Clearancementioning
confidence: 92%
See 2 more Smart Citations
“…These defects were also more prevalent with increasing severity of disease [12,14,19,20,26]. In contrast, Sondheimer [17] reported few motility defects in infants with GERD but found that these infants swallowed less frequently, particularly during sleep.…”
Section: Esophageal Volume Clearancementioning
confidence: 92%
“…In addition to changes in esophageal pressure wave propagation, severe GERD with reflux esophagitis is associated with a 30% to 50% decrease in pressure wave amplitude, indicating that the contractile strength of the esophagus is also impaired [12,14,15,19,20,26]. However, lower pressure wave amplitude does not necessarily lead to impaired clearance, as low peak amplitude pressure waves have been shown to be as effective as high peak amplitudes in facilitating bolus transit of liquids, provided that a threshold amplitude of greater than 20 mm Hg above intrabolus pressure is reached [38].…”
Section: Esophageal Volume Clearancementioning
confidence: 98%
See 1 more Smart Citation
“…It is more marked in those in whom gastric emptying is slow, or in those whose upper gastrointestinal motility is disordered as part of severe neurodevelopmental impairment (e.g. cerebral palsy) or because of cows' milk intolerance 35. Reflux is aggravated by chest physiotherapy and when oesophageal sphincter pressure is reduced by drugs such as theophylline or caffeine 6 , 7.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Sir: Although gastro-intestinal symptoms are common in neurologically impaired patients, there are limited data concerning possible motor dysfunction responsible for symptoms in these patients [3,4]. We therefore evaluated antroduodenal motility, gastro-oesophageal re¯ux (GOR), and lower oesophageal sphincter (LOS) pressures in 11 neurologically impaired children, adolescents and young adults who presented with vomiting, haematemesis, or abdominal distension.…”
mentioning
confidence: 99%